The Consumption of Relations and Loneliness amongst Adults - (:unkn) unknown (My University, 2020)
New forms of consumption have emerged with the appearance of the modern society.The money, which is seen as the commodity in this system, causes human beings to have aconstant need. Searching for goods on online shopping or in-store live shopping, one alwayslooks for pleasure and satisfaction. However, consciously or unconsciously that person getsconsumed. After sometime, isolation starts. In other words, this ends with estrangement. Theaim of this article is to find out at what age people feel lonely. In this article, the consumptionon the relations was examined amongst different age groups by using Differentiated LonelinessScale (DLS) developed by Schmidt N & Sermat V1.: The scale was used on two different agegroups consisting of 480 people; between 18 and 35-year-old and between 36 and 60-year-old.The research has some limitations due to using the scale on 480 people, totally.

Modern toplum sistemin ortaya çıkması ile yeni tüketim biçimleri ortaya çıkmıştır. Bu_x000D_ sistemde emtia olarak görülen para, insanoğlunun sürekli ihtiyaç hissetmesine sebep olmaktadır._x000D_ İnsan, mağaza içinde veya internet ortamında alışveriş yaparken daima zevk almayı, tatmin_x000D_ olmayı beklemektedir. Fakat o kişi bilinçli veya bilinçsizce tükenmektedir. Bir müddet sonra,_x000D_ toplumdan izole olma başlamaktadır. Diğer bir deyişle, bu durum yalnızlaşma ile bitmektedir._x000D_ Bu makalenin amacı insanların kendilerini hangi yaş gurubunda yalnız hissettiğidir. Makalede_x000D_ Schmidt N ve Sermat V tarafından geliştirilen Farklılaştırılmış Yalnızlık Ölçeği kullanılarak_x000D_ farklı yaş grupları arasındaki ilişkilerin tüketimi incelenmiştir. Ölçek 480 kişiden oluşan, 18_x000D_ ve 35 yaş grubu ile 36 ve 60 yaş üzerinde uygulanmıştır. Araştırma, ölçeğin 480 kişi üzerinde_x000D_ uygulanmasından dolayı bazı kısıtlılıklara sahiptir.
Yetişkinler Arasında İlişki Tüketimi ve Yalnızlık